2020
DOI: 10.1016/j.jnoncrysol.2019.119678
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of Nd3+-doped TeO2-TiO2-ZnO glasses with lower hydroxyl content

Abstract: This paper describes Nd 3+ -ions doped multicomponent tellurite glasses TeO2-TiO2-ZnO (TTZ) applicable to advanced optical devices, which were characterized by UV-Vis-NIR absorption, Raman, and photoluminescence (PL) techniques. Not only did we perform experimental characterizations but also theoretically predicted the PL properties of Nd 3+ -doped TTZ glasses by using the Judd-Ofelt theory. The influence of the residual hydroxyl (OH) groups and types of crucible used in the melt preparation on the structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The TZN glasses were also doped with 0.5%wt Nd 3+ ions to study photoluminescent properties of the glasses, which will be reported elsewhere. As the doping was small, the structural data given in this paper for the TZN glasses with different ZnO concentration are not affected by the Nd 3+ ions (28). Low-frequency Raman spectroscopy is applied to gain structural information of medium range of orders for the TZN glasses with constant TeO 2 content 80%mol and varying ZnO content from 0 to 20%mol, which shed light on how the network evolution of tellurite glasses is influenced by ZnO (covalent) and Na 2 O (ionic) entities.…”
Section: Introductionmentioning
confidence: 76%
“…The TZN glasses were also doped with 0.5%wt Nd 3+ ions to study photoluminescent properties of the glasses, which will be reported elsewhere. As the doping was small, the structural data given in this paper for the TZN glasses with different ZnO concentration are not affected by the Nd 3+ ions (28). Low-frequency Raman spectroscopy is applied to gain structural information of medium range of orders for the TZN glasses with constant TeO 2 content 80%mol and varying ZnO content from 0 to 20%mol, which shed light on how the network evolution of tellurite glasses is influenced by ZnO (covalent) and Na 2 O (ionic) entities.…”
Section: Introductionmentioning
confidence: 76%
“…Regardless of the limited laser source in our lab, the choice of this refractive index can compensate the refractive index difference arising from material dispersion, i.e., higher refractive index located at wavelength shorter than 650 nm and lower refractive index at longer wavelength. Perhaps for this reason, most works on Judd-Ofelt analysis published nowadays is based on such a single refractive index [27][28][29][30]. There are only few papers reporting Judd-Ofelt calculation by taking into account material dispersion [31].…”
Section: Judd-ofelt Analysismentioning
confidence: 99%
“…Tellurite glasses are good candidates for photonic applications because of their high linear refractive index, high dielectric constant, wide infrared transmittance, and high third-order nonlinear optical values as well as high solubility of rare-earth dopants. [1][2][3][4] Thus, a lot of works on luminescent rare-earth-doped tellurite glasses have been published [5][6][7][8][9] and a recent study is dedicated to development of downconversion phosphors of rare-earth-doped tellurite glasses for performance improvement of solar cells. [10] On the other hand, knowing the structural evolution of glasses is a difficult task that has sparked the interest of many researchers in the glass field.…”
Section: Introductionmentioning
confidence: 99%